Development of an mHealth trauma registry in the Middle East using an implementation science framework. Issue 1 (1st January 2017) - Mehmood, Amber; Chan, Edward; Allen, Katharine; Al-Kashmiri, Ammar; Al-Busaidi, Ali; Al-Abri, Jehan; Al-Yazidi, Mohamed; Al-Maniri, Abdullah; Hyder, Adnan A.
ABSTRACT: Background : Trauma registries (TRs) play a vital role in the assessment of trauma care, but are often underutilized in countries with a high burden of injuries. Objectives : We investigated whether information and communications technology (ICT) such as mobile health (mHealth) could enable the design of a tablet-based application for healthcare professionals. This would be used to inform trauma care and acquire surveillance data for injury control and prevention in Oman. This paper focuses on documenting the implementation process in a healthcare setting. Methods : The study was conducted using an ICT implementation framework consisting of multistep assessment, development and pilot testing of an electronic tablet-based TR. The pilot study was conducted at two large hospitals in Oman, followed by detailed evaluation of the process, system and impact of implementation. Results : The registry was designed to provide comprehensive information on each trauma case from the location of injury until hospital discharge, with variables organized to cover 11 domains of demographic and clinical information. The pilot study demonstrated that the registry was user friendly and reliable, and the implementation framework was useful in planning for the Omani hospital setting. Data collection by trained and dedicated nurses proved to be more feasible, efficient and reliable than real-time data entry by care providers. Conclusions : The initial results show the promising potential of a user-friendly, comprehensive electronic TR through the use of mHealth tools. The pilot test in two hospitals indicates that the registry can be used to create a multicenter trauma database.